Shortened Cervix in the Subsequent Pregnancy after Embolization for Postpartum Cervical Hemorrhage - Zoltan Kozinszky; Sverre Sand; Nils-Einar Kløw; Kirsten Hald (Hindawi Limited, 2014)
Introduction. Rupture of a branch of uterine artery during delivery often leads to a massive postpartum hemorrhage that can be successfully treated using uterine artery embolization. Case Report. A 33-year-old woman had a cesarean section at term followed by a secondary postpartum hemorrhage due to a ruptured cervicovaginal branch terminating in a large, partially thrombosed hematoma of the cervix. She was given selective uterine artery embolization, and she was discharged to home in stable condition on the third day after embolization. In the forthcoming pregnancy a shortened cervix was a risk of threatened premature delivery from 26 weeks of gestation onwards. Conclusion. Superselective unilateral embolization of a thrombosed hematoma in the cervix might prevent extensive iatrogenic trauma of the cervix, which allows preservation of reproductive function.